Intrahepatic Sarcomatous Cholangiocarcinoma: Case Report and Review of the Literature - Thana Boonsinsukh; Vichit Viriyaroj; Thammanij Rookkachart; Therdkiat Trongwongsa (Case Reports in Surgery)
The authors report a case of a patient with intrahepatic sarcomatous cholangiocarcinoma. A 45-year-old Thai man presented with a 3-month history of right upper abdominal pain. CT scan revealed hepatomegaly with a 6.5 cm hypovascular soft tissue density mass in the right lobe and showed mild delayed enhancement. On exploratory laparotomy, the tumor adherent to right diaphragm was found. We performed right hepatectomy, partial resection of right diaphragm, and cholecystectomy. The immunohistological results suggested “sarcomatous intrahepatic cholangiocarcinoma.” The tumor was recurrent in 5 months after operation and unresectable. Therefore, the treatment in this patient was supportive care. He died 11 months after his initial presentation. The literature reviews showed that intrahepatic sarcomatous cholangiocarcinoma is aggressive malignant with poor prognosis. Early detection, radical resection, and careful follow-up would be the treatment for the favorable prognosis.